Evaluation of the implementation of the HACCP system in the kitchen of Conrad Bali: A case study of food safety management in the hospitality industry - Ni Putu Eka Trisdayanti; I Made Purwa Dana Atmaja; Made Hendrayana (Bahasa Indonesia, 2026)
Food safety management is a critical concern in the hospitality industry, particularly in hotel kitchen operations where strict hygiene and quality standards must be maintained. Although the Hazard Analysis and Critical Control Points (HACCP) system is widely recognized as an effective approach to controlling food safety risks, empirical studies examining its practical implementation in hotel kitchens, especially in major tourism destinations, remain limited. This study aims to evaluate the implementation of the HACCP system in the kitchen of Conrad Bali and to identify key challenges, supporting factors, and opportunities for improving food safety management practices in the hospitality sector.This research employed a descriptive qualitative approach using semi-structured interviews with eight key informants, non-participant observation, and document analysis. The findings indicate that the HACCP system has been implemented systematically across kitchen operations, supported by staff understanding of HACCP principles, structured monitoring procedures, and consistent documentation practices. The implementation is further strengthened by adequate kitchen facilities, digital monitoring systems, regular internal audits, and strong management commitment. However, several operational challenges were identified, including logistical delays in sanitation supplies and staff adaptation due to trainee rotation. The study also highlights that waste segregation practices support both contamination control and sustainability initiatives. This research contributes to the understanding of HACCP implementation in hotel kitchens by demonstrating the importance of integrating food safety systems with digital monitoring and sustainability-oriented practices in the hospitality industry.